The Potential Association of CDKN2A and Ki-67 Proteins in View of the Selected Characteristics of Patients with Head and Neck Squamous Cell Carcinoma - Dariusz Nałęcz; Agata Świętek; Dorota Hudy; Zofia Złotopolska; Michał Dawidek; Karol Wiczkowski; Joanna Katarzyna Strzelczyk (Current Issues in Molecular Biology)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most prevalent type of cancer worldwide. Not all mechanisms associated with cell cycle disturbances have been recognized in HNSCC. The aim of this study was to examine the concentration of CDKN2A and Ki-67 proteins in 54 tumor and margin samples of HNSCC and to evaluate their association with the clinical and demographic variables. The ELISA method was used to measure concentrations of CDKN2A and Ki-67 in the tissue homogenates. A significantly higher CDKN2A concentration was found in OSCC tumor samples as compared with OPSCC+HPSCC+LSCC. An inverse correlation was observed for Ki-67. We showed an association between the CDKN2A level and the clinical parameters N in tumors. The patients with concomitant diseases had significantly higher levels of Ki-67 as compared with patients with no concomitant diseases. An analysis of the effect of drinking habits on Ki-67 level demonstrated a statistical difference between regular or occasional users of stimulants and patients who do not use any stimulants in the tumor and margin samples. Moreover, we found an association between CDKN2A and Ki-67 concentrations and the HPV status in tumor and margin samples. The levels of the proteins tested may be dependent on environmental factors. Our results showed that changes in protein levels in HNSCC subtypes may reflect different molecular pathways of tumor development or may also be responsible for the involvement of CDKN2A and Ki-67 in the carcinogenesis process.